MENYELESAIKAN MASALAH KELUARGA TANPA MELAKUKAN TINDAKAN KEKERASAN DALAM RUMAH TANGGA BERDASARKAN U.U. NOMOR 23 TAHUN 2003 TENTANG KDRT - Muzayanah Muzayanah (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
In living household and family life, of course, it is never separated from the problems that arise in the family itself. Every family member has rights and obligations that are protected by the state with the enactment of statutory provisions because Indonesia is a state of law. Rights and obligations that must be upheld by every human being within the family sphere, so it is necessary to foster legal awareness and public obedience to applicable laws. For this reason, so that the implementation of the Law on Domestic Violence (KDRT) will be successful, I hope that the residents of Prolanis Clinic